INTEGRASI TEKNOLOGI DAN MEDIA DALAM PEMBELAJARAN ABAD 21 DI PENDIDIKAN DASAR - Nadhifa Arufah Chafshah; Agus Pahrudin; Agus Jatmiko; Koderi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The integration of technology and media in 21st-century learning has become an important necessity in primary education to meet the needs of students in the digital era. The purpose of this research is to determine how the application of media and technology in teaching practices impacts student learning outcomes and engagement. Using qualitative descriptive methods, this research collects data through classroom observations, interviews with teachers and students, and document analysis. The results show that incorporating technology and media into an interactive and student-centered learning environment enhances their creativity, critical thinking skills, and collaboration abilities. In addition, teachers indicated that the use of digital platforms and media tools enhances the quality of learning. However, there are issues such as limited resources, lack of teacher instruction, and uneven access to technology. According to this research, the integration of technology and media in primary education can only be achieved with comprehensive infrastructure support and teacher training. This research provides educators and policymakers with important insights to determine future learning strategies.